Looking at the self: perspectival memory and personal identity. (2nd September 2019) - McCarroll, Christopher Jude
Abstract : Both Marya Schechtman and Galen Strawson appeal to autobiographical memory in developing their accounts of personal identity. Although both scholars share a similar conception of autobiographical memory, they use it to develop theories of personal identity that are radically distinct. Memories that are relevant for personal identity are generally considered to be personal (autobiographical) memories of those events in one's lifetime to which one can gain first-personal access: memories from-the-inside. Both Schechtman and Strawson base their discussion of personal identity on exactly this type of memory. Empirical evidence shows, however, that personal memory imagery is not only visualised from-the-inside, from a "field" perspective. Personal memories may also involve "observer" perspectives, in which one sees oneself from-the-outside in the remembered scene. Both Schechtman and Strawson appeal to the notion of remembering from-the-inside, but they remain silent on the phenomenon of observer perspectives in personal memory. I suggest that accounts of personal identity that appeal to memory should consider observer perspectives as one aspect of personal memory. I explore the implications that the acknowledgment and inclusion of observer perspectives would have for both Schechtman's and Strawson's accounts. Even though autobiographical memory is not their theoretical target, both Schechtman and Strawson base their accounts of personal identity on their understanding of autobiographical memory . Therefore, their depictions of the nature of personal identity are founded upon an incomplete picture of autobiographical memory.